The taxonomic status of Oligoryzomys brendae Massoia, 1998 (Rodentia, Cricetidae), with comments on the availability of this name - Teta, Pablo; Jayat, J. Pablo; Ortiz, Pablo E.; D’elía, Guillermo (Zootaxa, 2013)
Oligoryzomys brendae was poorly described by Massoia in 1998 to include populations of the large form of Oligoryzomys that inhabits the Yungas and high altitudinal grasslands of northwestern Argentina, which were previously referred as O. longicaudatus, O. stolzmanni, O. destructor or Oligoryzomys sp. Contrary to some interpretations, we state that the name O. brendae is available, given that it fully accomplishes the requirements of the International Code of Zoological Nomen-clature. We also present morphologic and genetic evidence showing that this taxon represents a distinct species and pro-vide an emended diagnosis and re-description of it. In addition, the evidence at hand indicates that O. brendae is the only large-sized species of Oligoryzomys inhabiting northwestern Argentina.